UPAYA PENGEMBANGAN UMKM DALAM PEREKONOMIAN INDONESIA - Berliana Ramadani (Jurnal Studi Akuntansi Pajak Keuangan, 2023)
The development of MSMEs in Indonesia has always increased every year and has an important role in the economy. This is what makes the government eager to help develop the businesses of MSME players by providing assistance, holding seminars, holding MSME festivals and so on. As an MSME actor, not only does he understand his business, but he should understand how to record his business accounting. The development of MSMEs in Indonesia can improve the quality of human resources by utilizing technology in the form of Instagram, Facebook, websites and other social media that can develop businesses widely. The purpose of writing this scientific work is to analyze MSME development efforts in the economy in Indonesia. Research shows that how big the contribution of MSMEs is in the Indonesian economy. In 2022 the growth of the Indonesian economy will reach 99% of all businesses, the contribution to GDP is 60.5% and in the workforce is 96.9% of the total national employment.